Psychological Impact of Derna Floods: A Comparative Study between Benghazi and Derna Medical Students - S. Salem, Asma; F. Benghasheer, Hala; O Alkhbulli, Yathrep; F. Alnasfi, Saud (Libyan Journal of Public Health Practices, 2024)
Psychological morbidities, including depression and anxiety, have been linked to flood exposure. The current study aimed to assess and compare the psychological effects of the Derna floods among medical students in the affected and non-affected areas and identify associated factors related to the crisis among medical students at Derna and Benghazi Universities. A cross-sectional study was conducted through a web-based questionnaire. The demographic characteristics, generalized anxiety disorder (GAD-7) scale, and patient health questionnaire (PHQ-9) scale were used to collect data. The data were analyzed using the Statistical Package for the Social Sciences (SPSS). All statistical analyses were performed at P < 0.05. A total of 707 completed web-based questionnaires were included in the analysis, of which female responses constituted 477 (67.5%) and male responses constituted 230 (32.5%). The prevalence of depression among students from Derna University was higher (76.0%) as compared to those from the University of Benghazi (64.5%). The depression score was significantly higher (P = 0.001) in Derna students (mean = 14.65, SD = 6.3) compared to Benghazi students (mean = 12.64, SD = 6.7). Derna students also had significantly higher anxiety scores (mean = 14.42, SD = 4.4) compared to Benghazi students (mean = 12.23, SD = 4.8, p = 0.0001). The mean score for depression was significantly higher among female and preclinical-year students (p = 0.0001). A startlingly high prevalence of anxiety and depression symptoms was evident among medical students after the Derna disaster. Effective intervention strategies are crucial in supporting the mental health of affected individuals and facilitating recovery and rebuilding.